2021
DOI: 10.1155/2021/8881605
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Investment in Carbon Emission‐Reducing Technology Based on Stochasticity and Low‐Carbon Preferences

Abstract: Due to excessive greenhouse gas emissions, carbon emission-reducing measures are urgently needed. Important emission-reduction measures mainly include carbon trading and low-carbon cost subsidies. Comprehensive consideration of these two policies is a research hotspot in the field of low-carbon technology investment. Based on this background, this paper considers the impact of consumer low-carbon preferences on market demand and the impact of uncertainty in carbon emission-reduction behaviour. We construct a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…According to the formula, it can be seen that the purpose of the objective function is to maximize the differentiation of D and minimize the difference between the distribution of G and the real data. Figure 1 depicts a schematic diagram of the structure of the generated adversarial network [21].…”
Section: Discriminative Methods Based On Generative Adversarial Networkmentioning
confidence: 99%
“…According to the formula, it can be seen that the purpose of the objective function is to maximize the differentiation of D and minimize the difference between the distribution of G and the real data. Figure 1 depicts a schematic diagram of the structure of the generated adversarial network [21].…”
Section: Discriminative Methods Based On Generative Adversarial Networkmentioning
confidence: 99%
“…Based on the consideration of the impact of consumers' low-carbon preference on market demand and the uncertainty of carbon emission reduction behavior, the stochastic differential game model of upstream and downstream enterprises is established. It is found that the government's cost subsidy policy can promote carbon emission reduction investment and improve supply chain profits [8]. Comprehensive fitness can enhance physique and improve health level [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the port supply chain, customers' low-carbon preference also plays a positive role in port emission reduction, but there is little research on this aspect. In the studies related to the product supply chain, Yu and Hou [18] investigated the influence of consumers' low-carbon preferences on the market demand. Su et al [19] built a pricing decision model in a green supply chain in line with consumer green preference, considering different forms of subsidy and various power structures.…”
Section: Literature Reviewmentioning
confidence: 99%